Knowledge and use of personal protective measures against mosquito borne diseases in a resettlement colony of Delhi - Anand, T; Ingle, GK; Kumar, R; Saini, V; Meena, GS (Annals of medical and health sciences research, 2014)
Mosquito borne diseases (MBDs) are major public health problem in India. State of Delhi is endemic for dengue and other MBDs. The increasing incidence of MBDs in Delhi in recent years warrants a pro-active approach for their prevention. Knowledge and use of personal protective measures (PPMs) presents an effective strategy for prevention and control of MBDs. The present study was conducted to assess the knowledge and use of PPMs against MBDs in an urban resettlement colony of Delhi. It was a cross-sectional study carried out in a resettlement colony of Delhi. A total of 100 families were selected by systematic random sampling. Data was collected using semi-structured questionnaire and supplemented by spot survey by the investigator in the community. The results were analyzed in SPSS version 16.0 (Chicago Illinios, USA). Out of the 100 respondents, 65% (65/100), 58%(58/100) and 13% (13/100) had heard about dengue, malaria and chikungunya, respectively. Nearly, one-fifth (20/100; 20%) of the participants reported incorrect breeding sites for mosquitoes. The knowledge regarding PPMs was very high (93/100; 93%) and about (90/100; 90%) families were actually using at least one of the PPMs. However, very few families were using them correctly (1/90; 1.1%) and adequately (5/90; 5.6%). The most common PPM being used by the study population was liquid vaporizers (54/90; 60%). Nearly one-third (29/90; 32.2%) of the participants reported side-effects due to PPMs with irritation to smell being the most common reported side-effect. On house visit, adult mosquitoes were seen in 67% (67/100) of the houses, while potential mosquito breeding sites were found in and around 56% (56/100) houses. There were crucial gaps in knowledge and practices of participants with regard to prevention and control of MBDs. Thus, there is a need to intensify efforts toward creating public knowledge and mobilizing community about correct use of preventive measures against MBDs.